PENGEMBANGAN MODEL PEMBELAJARAN SOFT SKILLS TERPADU DALAM PEMBELAJARAN PENJASORKES PADA SEKOLAH MENENGAH PERTAMA - Lilik Indriharta; S. Suharjana; M. Marzuki (Graduate School, Universitas Negeri Yogyakarta, 2016)
Tujuan penelitian ini adalah untuk: (1) mengembangkan model pembelajaran soft skills terpadu, (2) menganalisis keberhasilan pelaksanaan pembelajaran soft skills terpadu, dan (3) me-nganalisis dampak penerapan model pembelajaran Soft Skills Terpadu dalam pembelajaran Penjasorkes di Sekolah Menengah Pertama terhadap siswa. Penelitian ini merupakan penelitian pengembangan (Research Development). Subjek uji coba dalam penelitian ini adalah kelas VII pada 4 SMP Negeri di Kota Yoyakarta. Analisis data dilakukan secara deskriptif kualitatif dan kuantitatif. Hasil penelitian menunjukkan bahwa: (1) Tahap pengembangan model pembelajaran soft skills terpadu dalam pembelajaran Penjasorkes adalah tahap pendahuluan, pengembangan, dan evaluasi dengam hasil perangkat model berupa buku panduan, perangkat penilaian, dan instrumen pengembangan model pembelajaran. (2) Model pembelajaran soft skills terpadu dalam pembelajaran Penjasorkes menunjukkan tingkat keterlaksanaan yang tergolong sangat baik, memenuhi kriteria valid, sangat efektif, dan sangat praktis. (3) Model pembelajaran Soft Skills Terpadu dalam pembelajaran Penjasorkes di Sekolah Menengah Pertama mampu mengembangkan soft skills siswa.Kata kunci: model pembelajaran soft skills terpadu, pembelajaran pendidikan jasmani, olahraga, dan kesehatan, sekolah menengah pertama DEVELOPING INTEGRATED SOFT SKILLS LEARNING MODEL IN PHYSICAL EDUCATION, SPORT, HEALTH, AND RECREATION INSTRUCTION IN JUNIOR HIGH SCHOOLAbstractThis research is aimed at: (1) developing integrated soft skills learning model, (2) analyzing the success of integrated soft skills learning model implementation, and (3) analyzing the impact of the implementation of integrated soft skills learning model in physical education, sport, health, and recreation instruction on the students of junior high school. The research was a research adn development (R D). The subject of the research was students of grade VII in four junior high schools in Yogyakarta Municipality. Data analysis was conducted using qualitative and quantitative descriptive method. The result of the research shows that: (1) The stages of developing integrated soft skills learning model in physical education, sport, health, and recreation instruction include the stages of introduction, development, and evaluation which results model set in the form of handbook, assessment set, and instrument of learning model development. (2) Integrated soft skills learning model in physical education, sport, health, and recreation instruction reveals a very good level of implementation, fulfills the ‘valid’ citerion, is very effective and also practical. (3) Integrated soft skills learning model in physical education, sport, health, and recreation instruction in junior high school is capable to develop students’ soft skills.Keywords: integrated soft skills learning model; physical education, sport, health, and recreation instruction; junior high school